Taxpayers’ Perception of Public Sector Fiscal Responsibility and Voluntary Tax Compliance Behaviour in Rivers State, Nigeria - Osirim Monday (Journal of Accounting and Taxation, 2023)
This study which is on the influence of taxpayers' perception of  public sector fiscal responsibility on voluntary tax compliance is motivated by the quality of government fiscal responsibility, the level of tax compliance by the public and the reported low level of tax buoyancy and elasticity in Nigeria. The study adopts cross sectional survey research design.  Four hundred and three (403) copies of valid questionnaire were used for the study; this represents 85% of the respondents. The collected data were analyzed using both descriptive and inferential statistics. The proposed hypotheses for the study were tested using regression analysis. The study provides evidence to show that voluntary tax compliance is low in Rivers State, Nigeria as on the average, voluntary tax compliance produced a mean score of 2.0928 and standard deviation of 0.469592.The study also provides evidence indicating that public accountability, government fiscal transparency, balanced and surplus budget, public information dissemination and government public engagements are key drivers of voluntary tax compliance and their relationships with voluntary compliance are positive and significant. Hence, it could be reasonably concluded that voluntary tax compliance is lacking in Rivers State leading to the recommendations that revenue authorities in Rivers State, Nigeria should intensify efforts to identify,  register and bring to the tax net all eligible taxpayers operating in the formal and informal sectors by synergizing with financial firms and various professional bodies and trade unions. Public institutions should make public accountability and fiscal transparency their core mandate so as to earn public confidence  geared towards improved tax compliance behaviour.